CEREBRAL GLUCOSE UTILIZATION MEASURED WITH HIGH RESOLUTION POSITRON EMISSION TOMOGRAPHY IN EPILEPTIC FINNISH SPITZ DOGS AND HEALTHY DOGS. Issue 4 (18th February 2014) - Viitmaa, Ranno; Haaparanta‐Solin, Merja; Snellman, Marjatta; Cizinauskas, Sigitas; Orro, Toomas; Kuusela, Erja; Johansson, Jarkko; Viljanen, Tapio; Jokinen, Tarja S.; Bergamasco, Luciana; Metsähonkala, Liisa
<x xml:space="preserve">Abstract</x> In human epileptic patients, changes in cerebral glucose utilization can be detected 2‐deoxy‐2‐[18F] fluoro‐d‐glucose positron emission tomography (FDG‐PET). The purpose of this prospective study was to determine whether epileptic dogs might show similar findings. Eleven Finnish Spitz dogs with focal idiopathic epilepsy and six healthy dogs were included. Dogs were examined using electroencephalography (EEG) and FDG‐PET, with epileptic dogs being evaluated during the interictal period. Visual and semi‐quantitative assessment methods of FDG‐PET were compared and contrasted with EEG findings. Three independent observers, unaware of dog clinical status, detected FDG‐PET uptake abnormalities in 9/11 epileptic (82%), and 4/8 healthy dogs (50%). Occipital cortex findings were significantly associated with epileptic status (P = 0.013). Epileptic dogs had significantly lower standardized uptake values (SUVs) in numerous cortical regions, the cerebellum, and the hippocampus compared to the control dogs. The lowest SUVs were found in the occipital lobe. White matter normalized and left‐right asymmetry index values for all pairs of homologous regions did not differ between groups. Visual evaluation of the EEGs was less sensitive (36%) than FDG‐PET. Both diagnostic tests were consensual and specific (100%) for occipital findings, but EEG had a lower sensitivity for detecting lateralized foci than FDG‐PET. Findings supported the use of FDG‐PET as a diagnostic test for dogs with suspected idiopathic epilepsy. Visual and semiquantitative analyses of FDG‐PET scans provided complementary information. Findings also supported the theory that epileptogenesis may occur in multiple brain regions in Finnish Spitz dogs with idiopathic epilepsy.